Labour Share Fluctuations in Emerging Markets: The Role of the Cost of Borrowing - Serdar Kabaca (Bank of Canada, 2014)
This paper contributes to the literature by documenting labour income share fluctuations in emerging-market economies and proposing an explanation for them. Time-series data indicate that emerging markets differ from developed markets in terms of changes in the labour share over the business cycle. Labour share is more volatile in emerging markets and is procyclical, especially in countries facing countercyclical interest rates. In contrast, labour share in developed markets is more stable and slightly countercyclical. A frictionless small open-economy real business cycle model cannot account for these facts. I introduce working capital into this model, which generates liquidity need for labour payments. The main result is that the behaviour of the cost of borrowing can predict the right sign of the co-movement between labour share and output in both country groups, and can partly be responsible for the volatility of labour share. I also show that imperfect financial markets in the form of credit restrictions not only amplify the results for the variability of labour share but also help better explain some of the striking business cycle regularities in emerging markets, such as highly volatile consumption, strongly procyclical investment and countercyclical net exports.
Keywords: E25; F41; E44; 330; Business fluctuations and cycles; Labour markets; Development economics; International topics; Interest rates